Entrepreneurship in Portugal: comparison between the world bank data and quadros de pessoal - Sarmento, Elsa (2011)
Portugal has some of the highest business entry rates when compared to other countries, according to Eurostat, Statistics Portugal and the OECD Entrepreneurship Indicators Programme. We look at business creation in Portugal, from 2000 to 2007, by approaching two other complementary data sources, the World Bank Group Entrepreneurship Survey, based on official Portuguese business register’s and the universe of active employer enterprises, obtained by applying to the dataset Quadros de Pessoal, the methodology and definitions of the Eurostat/OECD´s “Manual on Business Demography Statistics”. This allows us to address entrepreneurship indicators comparability issues and exploit complementarities to support entrepreneurship patterns and trends previously identified by other national and international sources. We highlight the importance of considering information other than business registries, in particular when calculating business entry rates. Datasets where economically active units can be identified provide a better proxy for the true level of business creation and activity in Portugal.